Analisis Perceived Service Quality terhadap Loyalitas : Trust dan Satisfaction sebagai mediator - Wismantoro Yohan (Semantik, 2011)
Abstract : the research object is perum pegadaian cabang bulumanis. The purpose of this study to analyze the perceived service quality to customer satisfaction , customer loyalty and costomer trust. The research sampel of 100 responden with sampling techhnique is a non probability sampling . The result show thet perceived service quality has a positive and significant impace on customer satisfaction , perceived service quality has a positive and significant influence on customer loyalty, perceived service quality has a positive and significant influence on trust, customer satisfaction has a positive and significant influence on customer loyality and trust has a positive and significant influence on customer loyalty